Transformation of Work Practice in The Digitalized Labor Process: Freelancers in Turkey - KARATABAN, Melis; Ekiz Gökmen, Çisel (International Journal of Contemporary Economics and Administrative Sciences, 2022)
One of the most important changes created by the development of digital technologies in the global labor market is the spread of freelance work. This study aims to examine how freelance work has changed the working practices in Turkey, the motivations and working conditions of freelancers, the status of being a woman in freelance work, and the perceptions of women. For this purpose, in-depth interviews were conducted with 28 freelancers in Turkey. According to the field research findings, the education level of the interviewees is high and their freelance work experience varies between 1-12 years. It has been determined that while freelance work represents a precarious work on the one hand, it also offers a “free” working environment for the new generation labor with an entrepreneurial spirit, innovative and creative features. Although women are less visible than men in the freelance work, some of the male interviewees think that female freelancers are more successful in taking responsibility and creativity. Based on the discourses of the male interviewees towards female freelancers, it is possible to say that the majority of the male interviewees have developed a positive attitude towards gender equality.